Adjuvant radiation therapy for T4 non-rectal colon adenocarcinoma provides a cause-specific survival advantage: A SEER database analysis. (April 2019) - McLaughlin, Christopher; Kim, Nak-Kyeong; Bandyopadhyay, Dipankar; Deng, Xiaoyan; Kaplan, Brian; Matin, Khalid; Fields, Emma C.
Highlights: Adjuvant RT for non-rectal colon cancer is controversial, due to limited data. We used the SEER database to examine survival for T4 disease after adjuvant RT. We found a significant improvement in cause-specific survival with this treatment. Abstract: Purpose: While there is no level 1 evidence supporting the use of adjuvant radiotherapy (RT) for non-rectal colon cancer in the modern chemotherapy era, there are studies that suggest a local control benefit. This treatment modality is not part of standard treatment recommendations, and we hypothesized that adjuvant RT provides a benefit in locally advanced disease. Due to the limited number who receive post-operative RT, a national database was searched to provide sufficient power. Materials and methods: A retrospective analysis using the Surveillance, Epidemiology, and End Results (SEER) database was performed. Inclusion criteria were: non-rectal colon cancer, AJCC 6th or 7th edition T4 and M0, oncologic resection, and 1st cancer site. Patients were excluded for RT prior to or during surgery, or if the sequence of RT was unknown. Using a Cox proportional hazard model, the relative risk of cause-specific mortality for "RT after surgery" versus "No RT" was calculated. Results: 21, 789 patients were identified who met the inclusion criteria. Of these, only 1001 received adjuvant RT, and 64% were node-positive (53% RT vs. 65% no RT). When comparing RT vs. no RT, after adjusting for sex, age, N stage, and grade, we determined the relative risk of death from cancer was 0.8849 (95% CI: 0.8008–0.9779; p = 0.0165), suggesting that only 14 patients with T4 disease need receive adjuvant radiation to spare a cancer-related death. Conclusions: Adjuvant RT is not routinely utilized for definitive treatment of T4 non-rectal colon cancer, but this analysis shows a significant cause-specific survival benefit.